2014
DOI: 10.1002/mds.26093
|View full text |Cite
|
Sign up to set email alerts
|

Myorhythmia: Phenomenology, etiology, and treatment

Abstract: Myorhythmia is defined as repetitive, rhythmic, slow (1-4 Hz) movement affecting chiefly cranial and limb muscles. When occurring in the limbs it may be oscillatory and jerky, whereas oculo-masticatory myorhythmia, typically associated with Whipple's disease, is a slow, repetitive, often asymmetrical, facial and ocular movement. Thus, myorhythmia overlaps phenomenologically with tremor and segmental myoclonus. Although often present at rest, it must be differentiated from parkinsonian or dystonic tremor. Recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 93 publications
(276 reference statements)
6
87
0
Order By: Relevance
“…Terminology used in the literature has been somewhat inconsistent and contributes to some confusion about the movement disorders seen in CNS‐WhD. The term myorhythmia was introduced by Hertz in 1931, but its first use in the setting of WhD was by van Bogaert et al in 1963, who reported “oculofaciocervical myorhythmia” in a patient diagnosed 16 years later with CNS‐WhD . Some of the cases we reviewed predated that report.…”
Section: Discussion On Terminology: Myorhythmia and Myoclonusmentioning
confidence: 99%
“…Terminology used in the literature has been somewhat inconsistent and contributes to some confusion about the movement disorders seen in CNS‐WhD. The term myorhythmia was introduced by Hertz in 1931, but its first use in the setting of WhD was by van Bogaert et al in 1963, who reported “oculofaciocervical myorhythmia” in a patient diagnosed 16 years later with CNS‐WhD . Some of the cases we reviewed predated that report.…”
Section: Discussion On Terminology: Myorhythmia and Myoclonusmentioning
confidence: 99%
“…Myorhythmia has been recently defined as a repetitive, rhythmic, often jerky movement of slow (1–4 Hz) frequency, typically affecting the cranial and limb muscles16 although the term myorhythmia was originally coined by Herz17 in 1931. The movements of myorhythmia predominantly occur at rest and are distinguishable from a parkinsonian tremor by the lack of L-dopa responsiveness, a more irregular and slower frequency, as well as an intermittent nature.…”
Section: Unusual Tremor Syndromesmentioning
confidence: 99%
“…For instance, some of these tremors were predominantly described in patients with dystonia and would currently be more likely referred to as dystonic tremor 16. The main source of confusion results from the differential diagnosis with Holmes’ tremor or pseudorhythmic myoclonus, as these terms have been used interchangeably.…”
Section: Unusual Tremor Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically, myoclonus has been classified as cortical (e.g., cortical‐reflex myoclonus, epileptic myoclonus, and Alzheimer's disease), cortical‐subcortical (e.g., posthypoxic myoclonus, Huntington's disease [HD], and corticobasal degeneration), segmental (e.g., brainstem and spinal), or peripheral (e.g., hemifacial spasm). Myoclonus may be manifested by generalized, stimulus‐sensitive jerks, observed, for example, in patients with posthypoxic myoclonus, as small amplitude focal jerk‐like movements in epilepsia partialis continua, or slow, rhythmic, jerky movements present typically in brainstem or spinal segmental myoclonus, also referred to as myorhythmia …”
mentioning
confidence: 99%